Caracterização molecular e agressividade de isolados de Fusarium solani e Fusarium oxysporum f. sp. passiflorae e avaliação de híbridos interespecíficos, estimativa de prâmetros genéticos e ganhos de seleção visando a resistência - Marostega, Thalita Neves (2019)
Passion fruit is among the tropical fruits with great potential for cultivation in Brazil, showing marked expansion and popularization in domestic markets, across different sectors of consumption. Therefore, in recent years the culture, especially Passiflora edulis has been attracting investments in to expand its cultivated area. However, one of the major problems hindering the progress of P. edulis is its intolerance to soil phytopathogens, especially those that cause Fusariosis (Fusarium oxysporum f. sp. passiflorae) and Collar Rot (F. solani). The control of these diseases is preventive, because once affected by the pathogen, the plant rarely survives. Given the above, the objective of the research was to obtain and evaluate interspecific hybrids originating from the cross between Passiflora spp. and the families of P. edulis, aiming to develop cultivars of passion fruit resistant to Collar Rot and Fusariosis, for the state of Mato Grosso. The experiments were conducted in the experimental area of the Laboratory of Plant Genetic Improvement of the State University of Mato Grosso (UNEMAT) in Cáceres. First, a molecular and aggressiveness characterization was conducted of the isolates kept at the university library in order to select the most aggressive isolate of each pathogen and to carry out resistance tests on interspecific hybrids. Hybridizations were carried out using P. edulis and male genitors, P. nitida and P. mucronata, for crosses aiming at resistance to Fusariosis. P. nitida, P. cincinnata and P. quadrangularis hybridizations targeted resistance to collar rot. In addition, a test was carried out to confirm interspecific hybridizations with 35 microsatellite markers by PCR and agar gel electrophoresis. For the analysis of resistance to collar rot, the inoculation procedure was carried out with a mycelium disc fixed on a small wound on the stem of the plant and 10 characteristics of resistance were evaluated. The dissimilarity analysis was performed using the generalized distance of Mahalanobis (D2 ii") and a dendrogram was generated using the Ward grouping method. With regard to Fusariosis, the method of washed roots was used with analysis of the results through graphic dispersion. All endurance analyses were performed using the GENES computer program interacting with the "ape" R program package. Another recommended analysis was the estimation of genetic parameters in the hybrid population with resistance to Collar Rot, using the REML/BLUP procedure and methodology of the Genetic Design II of Comstock and Robinson. The Selegen software and the GENES program were used for this analysis. The results of the characterization of the isolates indicated molecular variability and aggressiveness among the isolates of each pathogen. The isolates FSUNEMAT 40 and FSUNEMAT 46 were selected for the tests of resistance to Collar Rot and the isolate FOUNEMAT22 for the fusariosis resistance tests. The interspecific crosses produced 49 F1 genotypes of passion fruit. The species that obtained the highest percentage of survival success with P. edulis in the crosses was P. nitida, with 8.05%. Confirmation of paternity when comparing the alleles of individuals from each progeny to the alleles of male and female parents identified a total of 28 individuals (57% of those obtained by interspecific hybridizations) with alleles of both parents. Through the dendrogram generated by the test of resistance to Collar Rot, it was possible to separate the study genotypes into four groups. Families 115 and 128 are promising genotypes for the next generation of the breeding program. In the evaluation of Fusariosis resistance F1 hybrids were separated into three groups, with genotypes 142 and 143- 2 being the most resistant. Through the REML analysis, it can be observed that the genotypic variance (σ2 g) was higher for AACALL (12,642,714) and AACELL (2017,330). For the estimates of phenotypic variance (σ2 f), it was observed that the variables AACEAL, AACECL, AACELL and NPM were explained almost entirely by σ2 g, a fact that contributes to increase the estimates of heritability and selective accuracy. High values for heritability estimates based on the average clone / genotypes (h2 mc) were noted for almost all characters, again emphasizing the variable AACEAL as having the highest heritability values (0.87). Selection through estimates of genetic gains predicted by BLUP made it possible to identify families 115, 143 and 113, with genotypes 113-1, 115-1, 115-7 and 143-1 as being the most resistant. Estimates of components of genetic variance for Delineation II showed that the female variance (σ2 f) presented negative values for all resistance characteristics analyzed and that the highest heritability values in the restricted sense were obtained for males. Thus, for the methodology of Comstock and Robinson II, the male genitor P. quadrangularis, the female P. edulis-113 and the family, 125, were selected as best breeders. It was concluded that the interspecific hybrids selected as resistant to both F. solani and F. oxysporum f. sp. passiflorae can be used as rootstocks and compose a backcrossing stage of the genetic breeding program targeting resistance to Collar Rot and Fusariosis of UNEMAT.